Pubertal development of body size and soccer-specific functional capacities in adolescent players - Moreira Carvalho, H.; Lekue, J. A.; Gil, S. M.; Bidaurrazaga-Letona, I. (Research in Sports Medicine, 2017)
Pubertal growth in body size and functional capacities were examined in adolescent soccer players (n = 33). The average age at baseline was 10.9 (9.8-11.8 years). Peak height velocity (PHV) and growth curves for body mass and functional performance (countermovement jump, 15-m sprint, agility and Yo-Yo intermittent recovery test - level 1) were determined with Bayesian multilevel models. Estimates for PHV and age at PHV were 8.1 cm/year (95% credible interval: 4.2-18.5 cm/year) and 12.9 years (95% credible interval: 11.8-15.5 years), respectively. Peak body mass velocity occurred 0.48 year after PHV. Jump performance maximum velocity occurred about 2 years after PHV and peak sprint performance maximum velocity was coincident with PHV. Agility and intermittent endurance run performance showed a quadratic trend of improvement of performance, starting to level off at about 3-4 years after PHV. The modelling procedures were efficient to determine pubertal growth curves aligned for chronological age and age at PHV, considering individual differences in maturation when interpreting the development of performance in youth soccer.